Saints' Lives as Performance Art. Issue 1 (24th June 2019) - Burrus, Virginia
Abstract : If scriptures are fundamentally textual in their semantic, performative, and iconic dimensions, as James Watts has argued, Saints' Lives are fundamentally performative, I suggest. The literary Lives of Saints are marked by a distinctive textual performativity, and icons – here not books, as for Watts, but painted images (eikones) and relics – are also distinctly performative qua objects, as expressed above all in an animistic capacity for intimate relationship. In a slight modification of Watts's nomenclature, we might then name the three performative dimensions of Saints' Lives the textual, the visual, and the thingly. Circulating through all of these dispersed media is the presence of the saint's body, at once vivid and elusive, unified and plural: the saint's performance is first and foremost a bodily performance, in all its dimensions. In order to develop this claim, I juxtapose passages from two late ancient literary Lives of Saints with contemporary performance art, moving on to consider more briefly the performativity of the visual and thingly dimensions of the lives of saints. Ultimately, we see not only how the line blurs between literary Life, on the one hand, and the life of a saint as it emerges across other media, on the other, but also how the three dimensions of the life – the textual, the visual, and the thingly – cross and converge.